중국 전기자동차 산업의 발전과 기술경쟁력 비교 분석 - 특허 통계를 중심으로 - 오새새; Saisai Wu; 최의현; Eui-hyun Choi; 최병헌; Byunghun Choi (중소연구, 2017)
중국의 전기자동차 판매량은 2015년 이후 미국을 넘어 세계 1위가 되었고, 정부는 자국 산업의 성장을 위해 전기차의 생산과 소비에 대한 보조금 지급을 확대하고 있다. 중국의 전기차 산업이 적어도 양적인 면에서는 그 성과를 내고 있다는 점에서는 별다른 이견이 없을 것 같다. 본 연구는 전기차 분야에서 중국 로컬 자동차의 기술 혁신과 기술경쟁력을 특허자료를 통해 분석하였다. 첫째, 정부 지원이 기술개발 보다는 생산과 수요를 늘리는데 집중되어 있었고, 투입된 자금에 비해 전기차 분야에서의 기술적 진보는 그리 높지 않은 것으로 나타났다. 구체적으로 특허 통계를 통해 분석해 보니 법적 효력을 가진 특허 등록보다 기술적 가치가 떨어지는 실용신안의 비율이 높았다. 둘째, 주요 기업별로 살펴보면 전반적인 전기차 특허에서는 지리, 창청 등이 비야디에 비해 더 많은 특허를 보유한 것으로 나타났지만 대부분 실용신안에 불과하였고, 주요 핵심 기술별 특허에서는 비야디를 제외한 다른 기업들은 별다른 특허를 보유하지 못하였다. 셋째, 한중일 삼국의 대표 전기차 기업인 현대, 비야디, 도요타를 대상으로 특허기술지수분석을 한 결과 도요타가 압도적으로 기술적 우위를 시현하였고, 비야디는 배터리 분야에서 상대적으로 많은 기술을 축적하였다. 이에 비해 현대는 특정한 기술 분야에서의 장점을 잘 보여주지 못하였다. 현대와 비야디의 전기차분야에서 글로벌 특허시장에서 경쟁력을 비교, 분석하면 두 회사의 차이는 그리 크지 않았다. 특허피인용지수 등 일부 기술지표에서는 비야디가 현대에 비해 기술적인 우위를 보이기도 하였다. 이는 향후 전기차가 좀 더 대중화 되고, 중국 자동차 시장이 전기차 중심으로 전환될 경우 중국내 한국산 자동차의 입지가 좀 더 위축될 가능성이 크다는 것을 의미한다. Since 2015 Chinese EV(electric vehicle) market has become the world largest market beyond the that of U.S. Chinese government enlarged their subsidies to support EV related industries and local consumptions. It is a common sense that Chinese EV car makers have shown pretty good performance at least in quantitative side. In the paper, we tried to analyze the technical innovation of Chinese local EV OEMs and technical competition between Korean, Chinese and Japanese car makers with the global patent database. First, we found the grant of money from government thorned into relatively enlarging supply and demand of local market than enforcing the R&D ability and technical progress of EV fields. According to the our findings, Chinese EV OEMs have possessed more ‘practical new devices’ than ‘registered patents’ which are legally protected by authorities and more technical intensive technology than the former. Second, Geely and Greatwall have had more EV patents than BYD, a well-known EV battery company in our investigation. However in case of the key technology fields, those two makers possessed fewer patents than BYD as we expected. Third, according to the patent analysis for three major car makers of Korea, China and Japan, Toyota showed dominant technical advantages in overall EV technology, BYD revealed relatively technical advantages in battery and unfortunately Hyundai did not proof any specialties in EV technology. Therefore if EV will be more popular than ever and will kick out the ICE(internal-combustion engine) in Chinese market, the Korean cars would confront more painful situation than now because between the technological distance of two countries in EV fields is closer than that of ICE sectors.